The impact of embryo binucleation depends upon its origin. Issue 1 (July 2020) - Gomes Paim, Lia Mara; FitzHarris, Greg
Abstract : Summary: Preimplantation embryos frequently contain binucleated cells, but reports differ as to whether binucleation affects development and whether such embryos should be used clinically. In this Point Of View article, we propose a possible explanation for this disparity: binucleation can arise by distinct routes, one that produces healthy blastomeres and one that directly threatens embryo viability.